Studies Regarding Leadership Approaches in Training Offers in the Face-To-Face and Online Context - Tita, Victor; Bold, Nicolae; Popa, Doinița; Matei, Mirela-Georgiana (Didactica Danubiensis, 2022)
The digital transformations that were present in the society have also extended to the education domain, both methodological and structural changes that were followed by several effects in the training market. Economically, the training market consists in the demand and offer of training courses, which have been modified in the aspects of topic and relation with the needs of the potential users. This paper aims to extend a study regarding the effects of the leadership type of the manager of the courses offering institution on the structure of courses with several effects of the digital transformation in the last period. In previous researches, the authors have determined several implications of the leadership type on the courses offer using a methodology based on literature review, a point of reference for the present paper. The study was structured on three main aspects: the determination of the offer structure by topic by determining the clusters of courses based on leader personality traits, the determination of the connection between the leadership style with the offer structure and the main transformation of the courses in the offer based on face-to-face and online learning forms by direct observation and analysis. The research was made on a cluster of seven teacher training houses in Romania in the school year 2021-2022. The results showed that the influence of the leadership style on the courses offer is a defined one and the last period has brought a normal change in the offer structure based on the online form of organisation.